Under the Adorned Dome, Four Essays on the Arts of Iran and India : Ehsan Yarshater Lecture Series - Porter, Yves (Arts and Archaeology of the Islamic World, 2023)
These essays are the revised and updated version of four lectures given in the Yarshater Lecture Series, at SOAS in London in 2013. They concern some aspects of the arts from pre-modern Iran and India, namely, the "making of" of Persian illustrated manuscripts, the iconography of Kashan wares, the use and re-use of luster tiles in Ilkhanid Iran, and the glazed tiles made in three Indian sultanates (Delhi, Bengal and Malwa). These four topics share concepts of influence and impact, although inflected on different modes. The productions they embody represent many poles of influence, even if working on different scales, from the extensive diffusion of products, techniques, and systems to almost isolated productions.